Distribution of scaled chrysophytes (Chrysophyceae and Synurophyceae) form the mesopotamia region of Argentina - Sueldo, Diana (2010)
Next to the Amazon, the Mesopotamia region of Argentina is a component of the second largest drainage basin in south America. It is an area of high biodiversity and contains important wetlands for migratory birds. the primary purpose of this study was to expand our knowledge of the scales chrysophyte flora of mesopotamia and to begin to investigate whether differences exist between specific subregions. Including this study, 42 scaled chrysophyte taxa have known tropical affinities. A preliminary analysis identified five groups of sites each containing discernible scaled chrysophyte flora. Some of the groups contained only sites from specific regions os mesopotamia and may represent geographic separation of this flora. further work is needed to fully understand the relative importance of such variables as spatial separation, water chemistry and habitats type in determining the distribution of scaled chrysophytes in this region of South America.